Azolla Plant Production and Their Potential Applications - Gamachis Korsa; Digafe Alemu; Abate Ayele (International Journal of Agronomy)
Globally, the human population is growing at an alarming rate, reducing land coverage over time. In the modern world, lifestyle changes, the nature of work, and food habits increase the incidence of serious diseases in animals, and human activity influences the environment, such as the use of chemical fertilizers for agriculture, large terrestrial ecosystems all over the biosphere, such as deforestation of plants, which could not sink from atmospheric CO2, and the production of fuels for energy, which would increase the need for fossil fuels but would also deliver low energy fuels at a high energy cost. To overcome the above problems, Azolla plants perform well since they can be grown at low labor costs, on small plots of land, and for a variety of purposes including animal feed/livestock, poultry and fish production, environmental remediation, biofertilizer and biocontrol for mosquito repellents, carbon sequestration of CO2, and bioenergy effectiveness all year. As a result of their low impact on the environment and human health, Azolla plants are becoming increasingly important. The purpose of this review is to provide evidence of Azolla plant production and its potential role in various applications for a greener, more sustainable approach. This review was progressive in that it assessed and produced peer-reviewed papers related to Azolla plant production and its potential role in different applications for a sustainable greener approach. Based on the findings of reputable educational journals, articles were divided into three categories: methods used to produce the nutritional composition of Azolla, environmental factors that affect the efficiency of Azolla plants, and strain improvement of Azolla for enhanced multipurposes and techniques that are currently being used to meet Azolla plants production and its prospective applications for different sustainable greener approaches. The present findings indicate that Azolla is a rich source of protein, which has a clear benefit in offsetting a portion of the nutritional needs of animal/livestock, poultry, and fish production with what is effectively a low-cost dietary supplement, biocontrol of mosquito repellent, environmental bioremediation, biofertilizer, carbon sequester of CO2, and bioenergy for the potential need of Azolla plant applications. Azolla plants have long been recognized for their benefits in greener and more sustainable lifestyles, as well as quality enhancement and bio-based economy over traditional approaches. Because it relied on natural resources and utility green production, this review’s recovery was chosen as an appropriate and environmentally sound solution for a long and healthy lifestyle.